Características vocais espectrográficas de crianças sem disfonia - Hoffmann, Carla Franco (2019)
Objective: to describe the maximum phonation times and the spectral acoustic vocal characteristics of children without dysphonia from 4:00 to 7:11 years of age and to correlate them with age, height and sex. Methods: transversal, quantitative, retrospective study in database. Data were collected on the height, sex and age of 299 children. The records of the maximum phonation times of the vowels / a /, / i /, / u / and of the vocal spectroscopy were analyzed. Results: positive correlation between harmonic replacement by noise at low frequencies and time of / a /; negative correlation between the intensity of the tracing of the fourth formant and the entire spectrogram and bandwidth of the first formant with the time of / u /; positive correlation between anti-resonance soon after the first formants and at high frequencies with time of / u /. In narrow band spectra, intensity, harmonic substitution by noise, definition and regularity of harmonics had a higher mean at low frequencies; the presence of noise was higher in the medium frequencies; number of harmonics and presence of higher sub-harmonics at high frequencies. In broad band spectra, the intensity was higher in the second formant; definition and width were greater in the first formant; regularity at low frequencies and anti-resonance were higher at high frequencies. No differences were found in narrowband and broadband spectra according to sex; most of the bandwidth measurements presented negative correlation with age and height, positive correlation between harmonic substitution by noise at low frequencies and time of / a /, negative correlation between intensity of the fourth formant throughout the spectrogram and width of the first formant with time of / u /, positive correlation between antiresonance soon after the first formants and at high frequencies with time of / u /. Conclusion: the maximum phonation times of the children were within the values of the literature and were influenced by height and age. Most of the spectrographic aspects evaluated were classified in a mild degree. Characteristics such as hoarseness, nasality and breathiness in a mild degree are considered normal for children, as occurred in this study. The increase in vowel time / a / showed a higher presence of noise and the increase of / u / showed increase of anti-resonance and lower color intensity of the tracing, evidencing loss of vocal quality with the time of support. Broadband and broad band spectra were not influenced by sex, but broad band measurements were influenced by height and age.